1980
DOI: 10.1111/j.1365-2222.1980.tb02147.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of P1‐antibodies in Scottish pigeon fanciers

Abstract: Summary The incidence and characteristics of P1‐antibodies in Scottish pigeon fanciers has been assessed. Of 223 individuals participating in the study, 23.3% were P1‐negative and of these, 53.9% had detectable P1‐antibodies. These antibodies were shown to belong to the IgM class and the highest serum levels were found in those pigeon fanciers with symptoms of respiratory disease who were sensitized to pigeon antigens. Of pigeon fanciers'; sera, 10.3% gave false positive reactions for the Hepatitis B surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…These will allow structural analysis of the immunological interactions at the molecular level. There is a glycolipid found in PDE which occurs on pigeon erythrocytes and which shows identity with the human P1 blood group substance [ 58, 59]. The antigenic structure of P1 is α galactose (1–4) β galactose (1–4) β N‐acetylglucosamine (1–3) β galactose (1–4) glucose ceramide.…”
Section: Disease Spectrum Associated With Pigeonsmentioning
confidence: 99%
“…These will allow structural analysis of the immunological interactions at the molecular level. There is a glycolipid found in PDE which occurs on pigeon erythrocytes and which shows identity with the human P1 blood group substance [ 58, 59]. The antigenic structure of P1 is α galactose (1–4) β galactose (1–4) β N‐acetylglucosamine (1–3) β galactose (1–4) glucose ceramide.…”
Section: Disease Spectrum Associated With Pigeonsmentioning
confidence: 99%
“…The study showed that the positive precipitating antibodies in the serum of individuals exposed to pigeon droppings are an important diagnostic parameter for PBD. However, the definitive diagnostic confirmation of PBD should be provided by bronchial challenge with pigeon dropping extract, which with its lower antigen concentration is safer than challenge by natural exposure (1,2,16). The existence of the so-called asymptomatic PBD form could not be confirmed by our study.…”
Section: Discussionmentioning
confidence: 64%
“…but also from other classes, e.g. IgM (14), or P1-antibodies (a variant of IgM) have been regularly detected in the patient's serum (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All antibody-antigen reactions were performed at 40°C to avoid possible reactions with any PI blood group antigen which may have been present in the avian material [12]. Optimal dilutions of materials and reagents were obtained by checkerboard titration.…”
Section: Methodsmentioning
confidence: 99%